Perfluorinated Acids in Arctic Snow: New Evidence for Atmospheric Formation - Young, Cora J; Furdui, Vasile I; Franklin, James; Koerner, Roy M; Muir, Derek C. G; Mabury, Scott A (Environmental science & technology, 2007)
Perfluorinated acids (PFAs) are ubiquitously found in water and biota, including remote regions such as the High Arctic. Under environmental conditions, PFAs exist mainly as anions and are not expected to be subject to long-range atmospheric transport in the gas phase. Fluorinated telomer alcohols (FTOHs) are volatile and can be atmospherically oxidized to form perfluorocarboxylic acids. Analogously, fluorosulfamido alcohols can be oxidized to form perfluorooctane sulfonate (PFOS). High Arctic ice caps experience contamination solely from atmospheric sources. By examining concentrations of PFAs in ice cap samples, it is possible to determine atmospheric fluxes to the Arctic. Ice samples were collected from high Arctic ice caps in the spring of 2005 and 2006. Samples were concentrated using solid-phase extraction and analyzed by LC−MS−MS. PFAs were observed in all samples, dating from 1996 to 2005. Concentrations were in the low−mid pg L-1 range and exhibited seasonality, with maximum concentrations in the spring−summer. The presence of perfluorodecanoic acid (PFDA) and perfluoroundecanoic acid (PFUnA) on the ice cap was indicative of atmospheric oxidation as a source. Ratios of PFAs to sodium concentrations were highly variable, signifying PFA concentrations on the ice cap were unrelated to marine chemistry. Fluxes of the PFAs were estimated to the area north of 65°N for the 2005 season, which ranged from 114 to 587 kg year-1 for perfluorooctanoic acid (PFOA), 73 to 860 kg year-1 for perfluorononanoic acid (PFNA), 16 to 84 kg year-1 for PFDA, 26 to 62 kg year-1 for PFUnA, and 18 to 48 kg year-1 for PFOS. The PFOA and PFNA fluxes agreed with FTOH modeling estimations. A decrease in PFOS concentrations through time was observed, suggesting a fast response to changes in production. These data suggest that atmospheric oxidation of volatile precursors is a primary source of PFAs to the Arctic.